Does Instagram and opinion makers influence on the consumer decision making and buying processes in the fashion and beauty industries? - Louro, Patrícia Neto Cordeiro Santos (2021)
The current dissertation has as main objective to perceive the role that the Digital Influencers present in Instagram, specifically in the Fashion and Beauty areas, have in the consumers’ decision-making process. Additionally, it also aims to characterise users and their habits on Internet, Social Media and Instagram, as well as to identify the advantages and disadvantages for the Influencers, to work with communication agencies. In order to obtain the results, it was planned to use two study’s types: quantitative, through the application of an online survey to Portuguese social network users, and qualitative, with the help of semi-structured interviews to the top 10 of Influencers with greater engagement in Fashion and Beauty industries. Among the main conclusions achieved with this work, it is confirmed that social networks have a strong presence in our daily life, namely Instagram, where most of the users follow influencers, mainly, in the Fashion and Beauty areas. In the same way, the main research objective was also assured, proving that Digital Influencers have an impact on the purchase intentions of their followers, however, with a higher level of influence on women than on men. It has also been proven that a positive eWoM has a greater effect on consumers, as most people can be influenced to buy a product or join a service, but only a few are influenced not to do so because someone told them it would not be worth it.